Physiological responses during the time limit at 100% of the peak velocity in the Carminatti`s Test in futsal players - Teixeira Floriano, L.; Fernandes da Silva, J.; Santiago Teixeira, A.; do Nascimento Salvador, P. C.; Dittrich, N.; Carminatti, L. J.; Loyola Nascimento, L.; Antonacci Guglielmo, L. G. (Journal of Human Kinetics, 2016)
The aim of this study was to investigate the physiological responses during the time limit at the intensity of the peak velocity of the Carminatti`s test (T-CAR). Ten professional futsal players (age, 27.4 ± 5.8 years, body mass, 78.8 ± 8.5 kg, body height, 175.8 ± 6.8 cm, body fat mass, 14.1 ± 2.6%) took part in the study. The players performed three tests, with an interval of at least 48 hours, as follows: the T-CAR to determine the peak velocity and the maximal heart rate; an incremental treadmill protocol to determine the maximal physiological responses; and a time limit running test at the peak velocity reached in the T-CAR. During the last two tests, a portable gas analyzer was used for direct measurement of cardiorespiratory variables. It was shown that the peak velocity was not significantly different from the maximal aerobic speed achieved in the laboratory (p = 0.213). All athletes reached their maximum oxygen uptake during the time limit test. The maximum oxygen uptake achieved during the time limit test was not different from that observed in the laboratory condition (51.1 ± 4.7 vs. 49.6 ± 4.7 ml·kg-1·min-1, respectively, p = 0.100). In addition, Bland and Altman plots evidenced acceptable agreement between them. On average, athletes took ~140 s to achieve maximum oxygen uptake and maintained it for ~180 s. Therefore, the peak velocity intensity can be used as an indicator of maximal aerobic power of futsal athletes and the time limit can be used as a reference for training prescription.